Testis expressed 50 is essential for maintaining sperm acrosome integrity during epididymal transit - Saori Haga; Kaori Nozawa; Ferheen Abbasi; Katarzyna Kent; Naoko Nagasawa; Tsutomu Endo; Haruhiko Miyata; Masahito Ikawa; Martin M. Matzuk; Yoshitaka Fujihara (Proceedings of the National Academy of Sciences, 2025)
In mammals, sperm formation is completed in the seminiferous tubules within the testis, and sperm maturation occurs during the epididymal transit of the spermatozoa. Sperm morphology drastically changes when abnormal spermatozoa migrate from the testis to the epididymis. Detailed molecular mechanisms for sperm survival in the epididymis have not been determined yet. Globozoospermia is a cause of male infertility and is characterized by round-headed spermatozoa without acrosomes, an abnormal sperm nuclear membrane, and sperm midpiece defects. Testis expressed 50 ( Tex50 ) is a testis-enriched gene that is expressed in mice and humans. Using CRISPR-Cas9, we generated Tex50 knockout (KO) mice and found that the KO males were sterile due to epididymal sperm malformations and impaired sperm motility. Surprisingly, electron microscopy, sperm morphology, and globozoospermia-related protein expression and localization in the KO testis were all normal. To understand this phenotype in more detail, we created TEX50-mCherry knockin mice to determine the localization of the TEX50 protein during spermatogenesis. The mCherry signals detected a ring-shaped structure surrounding the sperm acrosome and migrated to the posterior region of the sperm head. After the acrosome reaction, most of the spermatozoa retained mCherry signals. These results indicate that the Tex50 KO globozoospermia phenotype occurs after the migration of spermatozoa from the testis to the epididymis. We found that sperm membrane protein TEX50 is a putative key molecule to survive against globozoospermia-like malformations in the epididymis. It is essential for complete sperm formation and male fertility in mice.